Processos de licenciamento de pólos geradores de viagens: uma visão mais sustentável ao município de João Pessoa - Almeida, Brunna Lima de (2012)
The study of transportation systems describes various projects as potential points of attraction for the population; they are called Trip Generator. The process of attractiveness interferes directly triggered by developments in the transport system. Among the negative impacts it can be noted the concentration of the capacity of the transportation system. This impact on the transport system should be provided in the licensing process of Trip Generators. The methods adopted in Brazil to characterize them are traditional enterprises and encourage the use of private vehicles for transportation, prioritizing the provision of parking with capacity for this user profile. Changes have been observed in some developed countries, especially in Europe, about the politics of urban traffic management adopted in the evaluation of projects considered Trip Generator. This research analyzes an overview of some international and national licensing procedures exist for these enterprises, obtaining as a result of a comparison between the different processes and identifying the strengths and weaknesses. Adopting two different methodologies of authors who have studied indices and indicators for Sustainable Urban Mobility, an identification was made on to present which indicators can be influenced by the deployment of a Trip generator. From this identification are set forth actions that can be added to the licensing process in the city of João Pessoa which are in line with the new sustainable urban mobility policies developed by the Ministry of Cities.